First report of Burkholderia pseudomallei ST412 and ST734 clones harbouring blaOXA-57 but susceptible to imipenem in India. (November 2019) - Amladi, A.; Devanga Ragupathi, N.K.; Vasudevan, K.; Venkatesan, M.; Anandan, S.; Veeraraghavan, B.
Abstract: Melioidosis caused by Burkholderia pseudomallei has become an important clinical threat, especially in Northern Australia and Southeast Asia. However, the genome information on this pathogen is limited. B. pseudomallei isolates identified from bloodstream infections from inpatients were subjected to whole-genome sequencing by IonTorrent PGM and MinION Oxford Nanopore sequencing technologies. Highly accurate complete genomes of two strains, VB3253 and VB2514, were obtained by a hybrid genome assembly method using both short and long DNA reads. Both isolates carried bla PenI and carbapenemase-encoding bla OXA-57 genes, although the isolates were susceptible to imipenem by E-test method with MIC 1 μg/mL. Multiple IS family transposases specific for all non-fermenting Gram-negative bacteria (NFGNBs)—especially IS3 and IS5, which facilitate mobilization of extended-spectrum β-lactamase (ESBL) and carbapenemase genes—were carried in these genomes. This further adds to the complexity of gene transmission. These IS families were identified only upon hybrid genome assembly and would otherwise be missed.